Determination of whole-body tumour burden on [68Ga]PSMA-11 PET/CT for response assessment of [177Lu]PSMA-617 radioligand therapy: a retrospective analysis of serum PSA level and imaging derived parameters before and after two cycles of therapy - Michalski, Kerstin; Mix, Michael; Meyer, Philipp T.; Ruf, Juri (Nuklearmedizin - NuclearMedicine, 2019)
Aim In patients with metastasized castration-resistant prostate cancer a reliable imaging-based therapy response assessment in addition to PSA kinetics is desirable. Recently, measurements of whole-body tumour burden by [68Ga]PSMA-11 PET/CT have been reported for response assessment in oligometastasic patients. The present study investigated the association of PSMA PET derived parameters and serum PSA level before and after [177Lu]PSMA-617 radioligand therapy (RLT).Methods This retrospective study assessed whole-body PSMA tumour volume (PSMA-TV) in 10 patients with multifocal to diffuse metastases before and after 2 cycles of RLT using volume of interest (VOI) analysis. A standardized uptake value (SUV) threshold-based approach was used to semi-automatically delineate all voxels with a SUV ≥ 2.0 g/ml using the software ROVER® (ABX Radeberg, Germany). Voxels with physiological tracer uptake (e. g. kidneys) were excluded manually. Correlations between PSMA-TV and serum PSA level before and after two cycles of RLT as well as changes thereof (ΔPSMA-TV and ΔPSA, respectively) were calculated.Results Changes of ΔPSMA-TV and ΔPSA were concordant in 7 of 10 patients. Whereas a good correlation was found between PSMA-TV and PSA before RLT (ρ = 0.81, p = 0.0049), this correlation was attenuated after RLT (ρ = 0.64, p = 0.0479). Consequently, no association was found between ΔPSMA-TV and ΔPSA (ρ = 0.39, p = 0.26).Conclusion The attenuation of the correlation of PSA and PSMA-TV after RLT suggests that in patients with advanced disease the comparison of imaging based parameters such as PSMA-TV and PSA level might be useful for an adequate monitoring of treatment response.
Keywords: [68Ga]PSMA-11 PET/CT; [177Lu]PSMA-617 radioligand therapy; TL-PSMA; PSMA-TV; whole-body tumour burden